Multiplexed molecular profiling of lung cancer with malignant pleural effusion using next generation sequencing in Chinese patients - Ruan, Xingya (Oncol Lett, 2020)
Lung cancer is the most common type of cancer and the leading cause of cancer-associated death worldwide. Malignant pleural effusion (MPE), which is observed in ~50% of advanced non-small cell lung cancer (NSCLC) cases, and most frequently in lung adenocarcinoma, is a common complication of stage III–IV NSCLC, and it can be used to predict a poor prognosis. In the present study, multiple oncogene mutations were detected, including 17 genes closely associated with initiation of advanced lung cancer, in 108 MPE samples using next generation sequencing (NGS). The NGS data of the present study had broader coverage, deeper sequencing depth and higher capture efficiency compared with NGS findings of previous studies on MPE. In the present study, using NGS, it was demonstrated that 93 patients (86%) harbored EGFR mutations and 62 patients possessed mutations in EGFR exons 18–21, which are targets of available treatment agents. EGFR L858R and exon 19 indel mutations were the most frequently observed alterations, with frequencies of 31 and 25%, respectively. In 1 patient, an EGFR amplification was identified and 6 patients possessed a T790M mutation. ALK + EML4 gene fusions were identified in 6 patients, a ROS1 + CD74 gene fusion was detected in 1 patient and 10 patients possessed a BIM (also known as BCL2L11) 2,903-bp intron deletion. In 4 patients, significant KRAS mutations (G12D, G12S, G13C and A146T) were observed, which are associated with resistance to afatinib, icotinib, erlotinib and gefitinib. There were 83 patients with ERBB2 mutations, but only two of these mutations were targets of available treatments. The results of the present study indicate that MPE is a reliable specimen for NGS based detection of somatic mutations.